Determinants of patient and physician global assessment of disease activity and their discrepancies amongst South Africans with Rheumatoid Arthritis - Didi, Sariu Ali (Department of Medicine, 2025)
Background: Patient and physician global assessments (PGA and PhGA) play a crucial role in treatment decisions, yet discordance in these assessments is common. Factors influencing PGA and PhGA and discordance in South African (SA) RA patients remain poorly understood. Methods: This cross-sectional study included consenting adults with RA attending a tertiary hospital. Demographic, disease-specific, and patient-reported outcome data were collected. A discordance score was calculated by subtracting the PhGA score from the PGA score, and discordance was defined as PGA-PhGA ≥ 2.5. Determinants of PGA, PhGA, and determinants were explored using correlation analyses, linear regression, and logistic regression. Results: Of 550 patients, most were female (84.9%), with a mean (SD) age and disease duration of 55.8 (12.9) and 11.5 (9.7) years. Discordance was seen in 27.5%. Pain severity significantly influenced PGA, while tender and swollen joint counts predominantly influenced PhGA. A large portion of the variance in PGA and PhGA (62.0 % and 50.3% respectively) was unexplained. Patients with discordance reported higher pain scores, and problems with usual activities but had lower swollen joint counts and were more likely to be in remission or low disease activity than concordant patients. Conclusion: Discordance in patient-physician assessments exists in a considerable proportion of SA RA patients. Pain severity and functional limitations greatly influence patient perceptions. Addressing pain and activity limitations could help reduce discordance, optimize disease management, and foster shared decision-making. Further longitudinal and qualitative research is essential for a more comprehensive understanding of our RA patients' perspectives.